Evaluación del desempeño de un floculante orgánico para el tratamiento de las aguas de producción del campo B a nivel de laboratorio tomando como referencia la resolución 631 del 2015. (2021)
In the production water treatment process, various chemicals are used by means of which the final separation of traces of oil that may still be emulsified with the water is allowed, specifically this project focused on the evaluation of the type of flocculant which is currently used in field B to evaluate the possibility of implementing an organic flocculant that contains the same ease of decontamination of water with the benefit of reducing chemical loads used for this purpose.